BASIC ASPECTS OF DEVELOPMENT, INTRODUCTION, AND IMPLEMENTATION OF THE EXPERIMENTAL MODEL OF THE THIRD LEVEL OF HIGHER EDUCATION - Arnold Sterenharz; Natal'ya V. Ivanova (Высшее образование в России)
The article deals with the main aspects and prospects for development and implementation of the experimental model of the third level of higher education in engineering or technical sciences. The proposal of creation and design of information Web-based resource is discussed. Such Web resource will be based on knowledge bases, data warehouses and relationships between profiles of students, academic advisors and managers, subjects and information resources (electronic libraries and other information sources). The model and Web-based resource described in the article were proposed and discussed in frame of NETCENG Tempus project for introduction in universities of the Russian Federation, Ukraine and Belarus on the basis of the best international practices and in accordance with the trends of the Bologna process.